The design and implementation of speech controlled mobile robot - Abd Razak Bin Ahmad (Kulliyyah of Engineering, International Islamic University Malaysia, 2012)
This project involves with the study of Speech Controlled Mobile Robot where twowheeled robot is able to follow human speech direction commands, based on a vocabulary of around 10 words. An autonomous robot could be viewed as a special kind of service robot designed for personal use at home and industry. Robots designed for the home or office is a growing industry from both a research and commercial perspective. This thesis involves with the study of speech recognition mobile robot where the two-wheeled robot is able to follow human speech direction commands, based on a vocabulary of around 10 words. The primary inspiration of this project is come from PaPeRo and Wakamaru companion robot that are sold in the Japanese market amid the increasing growing number of old folks. The speech recognition mobile robot is programmed to perform basic direction movements based on certain simple human speech commands. At the same time, speech controlled mobile robot also have the ability of obstacle avoidance during the direction movements or patrolling in a house. Lastly, speech controlled mobile robot also could be served as personal Real Time Clock LCD Display to let people set time in seconds, minutes, hours, AM/PM, day, month, year and weekdays.